Development Of Contrast Enhancement Algorithm For Images Captured Under Insufficient Illumination - Huang, Nan (2017)
Many methods have been proposed to improve the contrast, quality and to optimize the insufficient illumination images. In the image enhancement, the main goal is to improve the contrast in the images. Images with high quality contain a great variety of information. The images quality is very easily affected by lighting, climate or equipment’s that have been used to capture the image. Some of these conditions such as insufficient illumination lead to darker images where the image may suffer information loss. Therefore, this thesis puts forward an optimized enhancement method in order to retain the information in the image. This proposed method performs on the insufficient light images. The proposed algorithm is decomposed by Haar wavelet to obtain the decomposition coefficient in all directions of the image, adjusts the threshold values of wavelet coefficient, then reconstruct the image. Finally, do the suitable postprocessing for the reconstructed image. The experimental results demonstrate that the proposed method successfully improves the image quality and contrast and these proven by a series of experiments. The proposed method shows good results for image enhancement. Whether it is in the image contrast enhancement, or extent of noise pollution. The proposed method was enhanced the contrast value more than fifty thousand at the same time, the variance was controlled less than ten thousand.